Development of inquiry based learning module for gravitation topic: need analysis - Razali, Fazilah; Mohd Ayub, Ahmad Fauzi; Zaini, Nourhaizum Awang (Faculty of Educational Studies, Universiti Putra Malaysia, 2024)
To achieve ambitious goals in a global setting, adopting educational reform needs new methods and plans to empower each student to acquire and excel in the essential skills for the 21st century. Teaching and learning practices are crucial in fulfilling the goal of the Malaysian education system to produce highly skilled and competitive students. This is a need analysis study for the first phase of Design and Develop Research (DDR). The purpose of this study was to determine the need to develop an inquiry-based learning module on physics form Four Gravitation topics. The study was carried out qualitatively, utilizing a semi-structured interview method conducted with four physics teachers selected under a purposive sampling technique. The data analysis employs thematic analysis, and the result was presented as thematic maps. The study has found four primary themes: (1) The importance of learning gravitation topic, (2) Challenges in teaching and learning gravitation topic, (3) Implemented teaching strategies for gravitation topic, and (4) Desired improvement of teaching strategies for gravitation topic. The analysis of the study's findings indicates a requirement to develop an Inquiry-based learning Module for the Gravitation topic. This module can potentially establish a student-centered learning environment that incorporates the essential components of 21st-century learning: critical thinking, creativity, communication, and values. Furthermore, teachers can vary the instructional methods used in the classroom to teach the concept of gravitation by guiding the development of modules.